An Introductory Study on Activated Carbon Monolith Electrodes Fabrication from Teak Leaf Waste - Taer, Erman (Journal of Technomaterial Physics, 2019)
A preliminary study has been conducted on supercapacitor carbon-electrode monolith prepared from teak leaf waste. The objective of this study is to know the electrochemical cell capacitance from carbon materials. The production of carbon electrode began with pre-carbonization process at 2500C for 2.5 hours, then proceeded to chemical activation using KOH activator with concentration of 0.3 M. Hydraulic Press was used with pressure at 8 ton to form the monolith. Then, the density was measured the carbonization. After that the sample was activated using CO2 gas at 8500C burning temperature. Next after the carbonization, the density was measured by collecting mass, diameter and thickness data of the electrode. The specific capacitance was measured using Physics CV UR Rad-ER 5481 which is controlled by a cyclic voltammetry software with the potential window width of 0 – 0.5 V and at a scan rate of 1 mV/s. The best density results obtained were 0.853 g/cm3 before carbonization for sample code C24 and 0.605 g/cm3 after carbonization for sample C30. The specific capacitance was found at 113.20 G/g for C32 and C38 electrodes